1998
DOI: 10.1007/bf01280875
|View full text |Cite
|
Sign up to set email alerts
|

Immunocytochemical localisation of auxin-binding proteins in coleoptiles and embryos ofZea mays L.

Abstract: Summary. The auxin-binding protein ABP-1 was localisedimmunocytochemically in coleoptiles and immature embryos of Zea mays. Two primary polyclonal antibodies raised against ABP-1 and secondary antibodies were either labelled with FITC or 10 nm gold particles for light microscopy, and with 10 nm gold particles for transmission electron microscopy. Light microscopy revealed that ABP-1 was localised in the epidermal cells of etiolated maize coleoptiles, in subepidermal parenchymatic mesophyll cells of the coleopt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…Maize ABP1 is a small, soluble glycoprotein with N-terminal signal peptide for entry into the secretory pathway and a C-terminal KDEL sequence for luminal endoplasmic reticulum (ER) retention [5,6]. Indeed, ABP1 has been found predominantly in the ER, and only a small part of its population is expected to escape through the secretory system to the outer face of the plasma membrane (PM) [7-10]. Because of the sharp pH optimum at 5.5 for binding of auxin to ABP1 [3], it is predominantly the apoplast/PM-residing fraction of ABP1 that is expected to act as an auxin receptor.…”
Section: Introductionmentioning
confidence: 99%
“…Maize ABP1 is a small, soluble glycoprotein with N-terminal signal peptide for entry into the secretory pathway and a C-terminal KDEL sequence for luminal endoplasmic reticulum (ER) retention [5,6]. Indeed, ABP1 has been found predominantly in the ER, and only a small part of its population is expected to escape through the secretory system to the outer face of the plasma membrane (PM) [7-10]. Because of the sharp pH optimum at 5.5 for binding of auxin to ABP1 [3], it is predominantly the apoplast/PM-residing fraction of ABP1 that is expected to act as an auxin receptor.…”
Section: Introductionmentioning
confidence: 99%
“…Many researchers have demonstrated its receptor function in mediating auxin-dependent cell division and expansion, such as in maize coleoptiles, shoots, and roots ( Henderson et al , 1997 ; Venis et al , 1992 ; Steffens et al , 2001 ), tobacco leaves and BY2 cells ( Chen et al , 2001 a ; David et al , 2007 ; Braun et al , 2008 ), and E. ulmoides stems ( Hou et al , 2006 ). It was shown that ABP1 present in the shoot meristem and the epidermal cells of the scutellum in maize immature embryos ( Bronsema et al , 1998 ). However, the lethality of the early globular-staged embryo in the mutant of ABP1 in Arabidopsis ( Chen et al , 2001 b ) prevents any further study of this gene in embryo development.…”
Section: Discussionmentioning
confidence: 99%
“…Previous work indicated that extracellular ABP1 has the function as a physiological receptor for cell expansion. ABP1 is usually stored in the endoplasmic reticulum and is secreted into the plasma membrane (PM) or the cell exterior via Golgi bodies ( Venis et al , 1992 ; Bronsema et al , 1998 ; Shimomura et al , 1999 ; Christian et al , 2006 ). By conditional expression of a single-chain fragment variable (scFv), which was derived from an antibody fragment directed against ABP1, endogenous ABP1 was inactivated and this led to the blocking of the cell cycle.…”
Section: Discussionmentioning
confidence: 99%
“…Immunology, molecular genetics and biochemistry techniques have shown that ABP1 can be stored in ER and secreted to the PM and the cell surface, where extracellular ABP1 functions to perceive the auxin signal and mediate the processes of inducible protoplast swelling and cell expansion observed at low levels of IAA (Bronsema et al, 1998;Chen et al, 2001a,b;Shimomura et al, 1999). Meanwhile, intracellular ABP1 might function in auxinregulated cell division (Chen et al, 2001b;David et al, 2007;Fellner et al, 1996).…”
Section: Possible Function Of Abp1 In Ovary and Ovule Developmentmentioning
confidence: 95%